Malabar in the Indian Ocean :cosmopolitanism in a maritime historical region - Mahmūd Kūria,Ed; Pearson, M. N.Ed (OUP, 2018)
Malabar is a crucial place in the Indian Ocean world, but its historical diversity is largely unexplored. Seafarers and writers have described it in terms of its own cultural and social life; however, a complete historical description of the engagement of the Arabs, Persians, Portuguese, Dutch, French and British has still not been attempted. Unlike the existing studies that rely heavily on European sources, Malabar in the Indian Ocean calls the attention of researchers to the rich trove of unknown or underutilized indigenous and foreign source materials in different languages, such as Malayalam, Arabic, Persian, Hebrew and Latin. In addition, it highlights certain materials that bear archaeological, epigraphical and architectural significance. Looking beyond the economics of the region and using translations of unpublished and rare sources, this volume highlights how the ocean has left a deep impact on the region’s society, culture, religion and politics, making it an exemplary cosmopolitan place.